Exosome may be the next generation of promising cell-free vaccines - Zelan Dai; Ruiru Cai; Hong Zeng; Hailian Zhu; Youwei Dou; Shibo Sun (Human Vaccines & Immunotherapeutics)
Traditional vaccines have limits against some persistent infections and pathogens. The development of novel vaccine technologies is particularly critical for the future. Exosomes play an important role in physiological and pathological processes. Exosomes present many advantages, such as inherent capacity being biocompatible, non-toxic, which make them a more desirable candidate for vaccines. However, research on exosomes are in their infancy and the barriers of low yield, low purity, and weak targeting of exosomes limit their applications in vaccines. Accordingly, further exploration is necessary to improve these problems and subsequently facilitate the functional studies of exosomes. In this study, we reviewed the origin, classification, functions, modifications, separation and purification, and characterization methods of exosomes. Meanwhile, we focused on the role and mechanism of exosomes for cancer and COVID-19 vaccines.